Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the value of [tex]\( b \)[/tex] given the functions [tex]\( f(x) = x^3 - 3 \)[/tex] and [tex]\( f^{-1}(x) = \sqrt[3]{x - 3b} \)[/tex], we need to ensure that the composition of the function [tex]\( f \)[/tex] with its inverse [tex]\( f^{-1} \)[/tex] returns [tex]\( x \)[/tex]. Specifically, we want:
[tex]\[ f(f^{-1}(x)) = x \][/tex]
Start by substituting [tex]\( f^{-1}(x) \)[/tex] into [tex]\( f \)[/tex]:
[tex]\[ f(f^{-1}(x)) = f(\sqrt[3]{x - 3b}) \][/tex]
We know that:
[tex]\[ f(x) = x^3 - 3 \][/tex]
Therefore, substituting [tex]\( \sqrt[3]{x - 3b} \)[/tex] for [tex]\( x \)[/tex] in [tex]\( f(x) \)[/tex]:
[tex]\[ f(\sqrt[3]{x - 3b}) = (\sqrt[3]{x - 3b})^3 - 3 \][/tex]
Simplify the expression inside the function:
[tex]\[ f(\sqrt[3]{x - 3b}) = x - 3b - 3 \][/tex]
To satisfy [tex]\( f(f^{-1}(x)) = x \)[/tex], the right-hand side must equal [tex]\( x \)[/tex]:
[tex]\[ x - 3b - 3 = x \][/tex]
Subtract [tex]\( x \)[/tex] from both sides:
[tex]\[ -3b - 3 = 0 \][/tex]
Solve for [tex]\( b \)[/tex]:
[tex]\[ -3b = 3 \][/tex]
[tex]\[ b = -1 \][/tex]
Therefore, the correct value of [tex]\( b \)[/tex] is:
[tex]\[ \boxed{-1} \][/tex]
[tex]\[ f(f^{-1}(x)) = x \][/tex]
Start by substituting [tex]\( f^{-1}(x) \)[/tex] into [tex]\( f \)[/tex]:
[tex]\[ f(f^{-1}(x)) = f(\sqrt[3]{x - 3b}) \][/tex]
We know that:
[tex]\[ f(x) = x^3 - 3 \][/tex]
Therefore, substituting [tex]\( \sqrt[3]{x - 3b} \)[/tex] for [tex]\( x \)[/tex] in [tex]\( f(x) \)[/tex]:
[tex]\[ f(\sqrt[3]{x - 3b}) = (\sqrt[3]{x - 3b})^3 - 3 \][/tex]
Simplify the expression inside the function:
[tex]\[ f(\sqrt[3]{x - 3b}) = x - 3b - 3 \][/tex]
To satisfy [tex]\( f(f^{-1}(x)) = x \)[/tex], the right-hand side must equal [tex]\( x \)[/tex]:
[tex]\[ x - 3b - 3 = x \][/tex]
Subtract [tex]\( x \)[/tex] from both sides:
[tex]\[ -3b - 3 = 0 \][/tex]
Solve for [tex]\( b \)[/tex]:
[tex]\[ -3b = 3 \][/tex]
[tex]\[ b = -1 \][/tex]
Therefore, the correct value of [tex]\( b \)[/tex] is:
[tex]\[ \boxed{-1} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.